2015
DOI: 10.1242/dev.123208
|View full text |Cite
|
Sign up to set email alerts
|

Ttk69 acts as a master repressor of enteroendocrine cell specification inDrosophilaintestinal stem cell lineages

Abstract: In adult Drosophila midgut, intestinal stem cells (ISCs) periodically produce progenitor cells that undergo a binary fate choice determined primarily by the levels of Notch activity that they receive, before terminally differentiating into enterocytes (ECs) or enteroendocrine (EE) cells. Here we identified Ttk69, a BTB domain-containing transcriptional repressor, as a master repressor of EE cell specification in the ISC lineages. Depletion of ttk69 in progenitor cells induced ISC proliferation and caused all c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

7
76
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 39 publications
(83 citation statements)
references
References 50 publications
7
76
0
Order By: Relevance
“…On the other hand, knockdown of ttk69 allowed Su(H) C EBs to differentiate toward EE cells, indicating that Ttk69 functions to prevent EC-committed EB from adopting EE cell fate. Moreover, 15 Taken together, these observations are consistent with a role for Ttk69 as a master EE cell fate repressor, but not an EC fate promoter.…”
supporting
confidence: 68%
See 4 more Smart Citations
“…On the other hand, knockdown of ttk69 allowed Su(H) C EBs to differentiate toward EE cells, indicating that Ttk69 functions to prevent EC-committed EB from adopting EE cell fate. Moreover, 15 Taken together, these observations are consistent with a role for Ttk69 as a master EE cell fate repressor, but not an EC fate promoter.…”
supporting
confidence: 68%
“…1C). 15 Therefore we concluded that Ttk69 but not Ttk88 regulates EE cell specification from progenitor cells. We further studied the genetic relationship between Ttk69 and Notch signaling in EC/ EE cell specification.…”
mentioning
confidence: 79%
See 3 more Smart Citations